Denotative and Connotative Meaning in One direction’s Songs Lyric: A Semantic Perspective - Arsiska Sari; Paramita Kusumawardhani (ELT-Lectura, 2016)
The purpose of this analysis is to find out some words that contains with connotative anddenotative meaning on specific object in the three one direction’s songs lyric based on Withers and Keami(2003) as the activity in semantic class. The data was taken from the text, found in the three different songslyric:“Hey Angel”, “Long Way Down”, and “Drag me Down” by One Direction in their album “Make in theA.M”. Descriptive qualitative employed as the method in this research. After analyzing the data found fromthe lyrics, this study found that (1) Some lyrics contained with connotative and denotative meaning onreferrring a specific object, (2) Connotative meaning found more dominant compare than dennotativemeaning.